Identifying synergies and complementarities between MDGs: Results from cluster analysis - Maria Carmela Lo Bue; Stephan Klasen (Georg-August-Universität Göttingen, Courant Research Centre - Poverty, Equity and Growth (CRC-PEG), 2012)
The MDGs are interlinked: acceleration in one goal is likely to speed up progress in others. Nevertheless, these synergies are not always visible, and may differ across countries. Using bivariate cluster analysis, this paper investigates whether distinct groups of developing countries can be identified, using statistical methods, on the basis of the correlation of changes in main MDG indicators over the 1990-2008 period. Potential groups include: [1] 'good performers', characterized by strong positive synergies in MDGs indicators; [2] 'poor performers', where there are synergies in poor progress towards the MDGs and [3] 'partial performers' countries where progress in one MDG went along with regress or stagnation in another. We then study the determinants of cluster membership. While growth in GDP per capita is, unsurprisingly, best able to distinguish between 'good' and 'poor' performers, a poor institutional framework and deteriorations in the income distribution is a notable correlate of partial progress, thus apparently undermining synergies in reaching the MDGs. In light of the current discussions about the post-MDG system, our results suggest that synergies between MDG progress can be achieved but they cannot be taken for granted. Improving institutional performance and reducing inequality appear particularly important drivers of promoting such synergies.
Keywords: O15; C38; 330; Millennium Development Goals; Human Development; Cluster Analysis